LEGAL ASPECT OF ELECTRONIC MEDICAL RECORDS - Edi Wahjuni; Nuzulia Kumala Sari (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Electronic medical records are needed in healthcare facilities for the hospital’s complete, accurate and real-time data required to improve an optimum, efficient and integrated health care. Electronic documents can be used as legal evidence based on Article 5 paragraphs (1) and (2) of Law Number 11 The year 2008 on Electronic Information and Transactions stating that electronic documents are legal evidence that is lawful and they are the expansion of legal evidence. Electronic documents are considered valid if the system is in accordance with the provision of Article 5 paragraph (3) of Law Number 11 The year 2008 on Electronic Information and Transactions.Keywords: evidence, electronic and medical records